Missing Twin Syndrome: life after perinatal mourning. - Zampi, Rita (Phenomena Journal - International Journal of Psychopathology, Neuroscience and Psychotherapy, 2023)
The aim of this study is to investigate a psychological phenomenon that is experienced by a fetus in perinatal phase, or the loss of a twin. The interest in this topic stems from a clinical case that I followed in the psychotherapeutic path, through which I discovered the existence of a world within the uterus of which we still have little knowledge. This is the "Syndrome of the Missing Twin", dealing with those deaths called "silent" that occur in the perinatal period, of which the mother has no awareness but the embryo that remains alive. This syndrome means the disappearance of an embryo in twin pregnancies confirmed by an ultrasound. Empirical research states that the latter already inside the uterus is capable of memorizing, learning, experiencing emotions and based on these experiences and the bond of attachment with the mother, will begin to build a prenatal memory that will carry with him throughout his life in an unconscious way. The emotional repercussions of a surviving twin vary from case to case. The numerous testimonies collected by the Austermann couple help us to understand how a widespread phenomenon is and to which little attention is still paid in the scientific world.